OPTIMIZATION OF INSULATED HfO2 DIELECTRICS OF GaN/InN/GaN/ In0.1Ga0.9N ENHANCEMENT MODE OF MIS-HEMT HETEROSTRUCTURE FOR HIGH FREQUENCY POWER AMPLIFIER APPLICATIONS (Nigerian Journal of Technology, 2019)
In this paper, the enhancement-mode operation of the hetestructure of GaN/InN/GaN/In0.1Ga0.9N of the Metal Insulator Semiconductor High Electron Mobility Transistor (MIS-HEMTs) device having lnN-channel was investigated. The effect of scaling the device dimensions of Metal Insulator, such as the dielectric thickness of HfO2 and the channel lengths, on the electrical performances was analyzed and compared to the currently used heterostructure. The numerical simulation of synopsis TCAD used showed a significant improvement in the electrical properties of the device that achieved a threshold voltage (VT) = 0.828 maximum drain current of 1.77 A/mm V, transconductance (gm) of 2.29 S.mm?1, lowest ON-state resistance (RON) of 0.21 ?.mm, and along with high-frequency performance achieving fT/ fmax of 98 GHz/129 GHz and 200 GHz/ 360 GHz respectively. The simulations also showed that this scaled GaN/InN/GaN/In0.9Al0.1N heterostructure MIS-HEMT is an excellent substitute to the currently used MIS-HEMTs for delivering high power density and frequency at RF/power amplifier applications. http://dx.doi.org/10.4314/njt.v38i2.29